2018
DOI: 10.1016/j.ijheatmasstransfer.2018.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Pool boiling in deep and shallow vessels and the effect of surface nano-texture and self-rewetting

Abstract: Pool boiling of ethanol and self-rewetting fluids on bare copper surface and copper surface with polymer nanofibers were studied experimentally. No significant effect of the depths of ethanol layer on the heat removal rate was found. That indicates that only the heat transfer in the liquid microlayer near the heater surface is a dominant factor. As a result, one can expect that selfrewetting fluids can significantly affect boiling performance. Accordingly, several alcohol solutions including the self-rewetting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Most research is focused on developing functionalized surfaces for boiling enhancement through surface engineering methods, by changing the surface morphology and their interaction with the boiling fluid [3,[5][6][7]. Boiling surfaces tailored toward enhancement of boiling performance are highly required in industrial applications [8,9]. The performance of boiling surfaces depends on a variety of interconnected factors, such as roughness, topology, porosity, wettability, wickability and others [10][11][12][13] and might vary in time due to surface aging, fouling, oxidation or contamination [3,11,[14][15][16][17].…”
Section: Basics Of Boiling Heat Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…Most research is focused on developing functionalized surfaces for boiling enhancement through surface engineering methods, by changing the surface morphology and their interaction with the boiling fluid [3,[5][6][7]. Boiling surfaces tailored toward enhancement of boiling performance are highly required in industrial applications [8,9]. The performance of boiling surfaces depends on a variety of interconnected factors, such as roughness, topology, porosity, wettability, wickability and others [10][11][12][13] and might vary in time due to surface aging, fouling, oxidation or contamination [3,11,[14][15][16][17].…”
Section: Basics Of Boiling Heat Transfermentioning
confidence: 99%
“…Although negligible in the boiling of single-component fluids [52], Marangoni flow significantly affects the boiling performance in dilute mixtures of alcohols (with four and more carbon atoms) in water [53,54]. These mixtures were named self-rewetting fluids (SRFs), as solutal Marangoni flow is expected to be further enhanced by thermal Marangoni flow, and the inflow of colder liquid spontaneously rewets hot places during boiling due to surface tension gradients induced by temperature inhomogeneities inside the boiling liquid [9,52,54].…”
Section: Self-rewetting Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a cheap method of surface functionalization, simple to apply and suitable for various materials and geometries. Sankaran et al [25] emphasize that low-cost, simple and straightforward methods for the manufacturing of micro-or nanoscaled textured surfaces for boiling applications with a scale-up potential are highly desired. Kim et al [26] point out that microstructures are rarely applied in the industry due to the higher costs and need for special materials.…”
Section: Surface Roughness and Topographymentioning
confidence: 99%
“…Zhou et al [51] investigated boiling enhancement using a combination of a copper foam and a 1-butanol-based SRF, finding that a very slight heat transfer intensification could be achieved using the densest foam in combination with the SRF. Sankaran et al [25] covered copper surfaces with polymer nanofibers and found that using a 1-heptanol-based SRF on such surfaces can provide a small additional HTC enhancement but decreased the CHF values compared with the boiling of pure water. In general, the results of previous studies suggest that a small additional enhancement of boiling performance can be achieved using SRFs on modified surfaces, but no tests seem to have been performed on surfaces with hydrophobic properties.…”
Section: Boiling Of Srfs On Modified Surfacesmentioning
confidence: 99%